Potential predictors of detrusor underactivity in a urology outpatient clinic: a 5-year single center experience study (Medical Journal of Indonesia, 2021)
BACKGROUND Detrusor underactivity (DU) is diagnosed using urodynamics, which caused by a combination of strength and duration of the bladder muscle and resulted in prolonged bladder emptying. Invasive urodynamics, which are limited in many clinical settings, should be performed efficiently in high-risk patients to reduce the risk of emerging complications during and after the procedure. Therefore, this study was aimed to identify the potential predictors of DU for limited clinical settings. METHODS This retrospective study was retrieved from the medical records of patients who underwent urodynamics in the Department of Urology, Cipto Mangunkusumo Hospital from 2015 to 2020. Age, sex, bladder capacity, bladder compliance, bladder outlet obstruction, history of stroke, diabetes mellitus (DM) status, and neurological abnormalities were analyzed using chi-square and Mann–Whitney to examine the potential predictors of DU. The odds ratio (OR) of each factor was also calculated. Logistic regression was furtherly used for the analysis. RESULTS A total of 649 patients were included in this study. Male (OR = 1.74, 95% CI = 1.28–2.38) and DM patients (OR = 2.06, 95% CI = 1.36–3.11) had a higher risk of DU, while bladder outlet obstruction (OR = 0.54, 95% CI = 0.39–0.76) was the protective factor of DU. Furthermore, multivariate analysis showed that the potential predictors of DU were male (OR = 1.903, 95% CI = 1.37–2.64), DM (OR= 1.899, 95% CI = 1.22–2.95), and bladder outlet obstruction (OR = 0.32, 95% CI = 0.32–0.65). CONCLUSIONS Age, sex, bladder outlet obstruction, and history of DM could become the predictors of DU.